Problems Of Teaching Preschoolers To Communicate - Boyboriyeva Saodat Oralovna (Periodica Journal, 2024)
Three- to five-year-old children still have a need for affection, understanding and communication from adults. Confidence-based communication with adults and the ability to feel his emotional state (joy, pleasure, sadness, calmness, anger, etc.) and to understand the reasons for mood changes develop.
Keywords: communication; confidence; preschool age